The role of serum monounsaturated fatty acids (MUFAs) and polyunsaturated fatty acids (PUFAs) in cardiovascular disease risk - Kharazmi-Khorassani , Jasmin; Ghafarian Zirak , Roshanak; Ghazizadeh , Hamideh; Zare-Feyzabadi , Reza; Kharazmi-Khorassani , Sara; Naji-Reihani-Garmroudi, Sharzad; Kazemi , Elham; Esmaily , Habibollah; Javan-Doust, Ali; Banpour, Hamed; Mohammadi-Bajgiran, Maryam; Besharatlou, Mohhamad reza; et al. (Acta Biomedica Atenei Parmensis, 2021)
Abstract Background: Fatty acids have been observed as independent risk factors of cardiovascular diseases (CVD). In this study we investigated FFA levels in patients with CVD, and, its risk factors. Material and Methods: In this case-control study, 346 unrelated Iranian patients who underwent coronary angiography were enrolled. Participants were categorized into two groups: who had >50% stenosis were assigned to the angiogram positive group (N=90) and those with <30% stenosis were assigned to the angiogram negative group (N=124) and also 222 subjects were healthy. Several risk factors were assessed in all participants, including anthropometric indices, blood pressure, lipid profiles, and biochemical factors. The levels of FFAs were determined using gas chromatography. Serum FFA concentrations were compared between healthy and patients with positive and negative angiograms. The association of serum FFA levels with four major risk factors (hypertension, high fasting blood glucose (FBG) level, high BMI and WHR) were also assessed. Results: According to our data, it has been shown that median of FFAs was higher in patients than healthy subjects (p<0.0001), such as SFA and n6-FFAs (in patients 1.59 (1.27) and 1.22 (1.06), respectively and healthy subjects 0.33 (0.38) and 0.36 (0.35)). According to anthropometric and biochemical data, we did not show statistical differences between the groups, except FBG, SBP and hs-CRP that showed significantly higher levels in the patients than controls (p<0.0001, p=0.001). Also, lower median levels of total cholesterol, LDL-C, HDL-C and DBP were observed in patients which can due to lipid-lowering medication use like Statins. Conclusion: High serum levels of FFAs are considered as an independent risk factor for CVDs, while various types of FFAs can have different influences on CVD risk factors. Therefore, longitudinal studies are needed to clarify the association between FFAs and CVD risk factors. High serum levels of FFAs are considered as an independent risk factor for CVDs, while various types of FFAs can have different influences on CVD risk factors. Therefore, longitudinal studies are needed to clarify the association between FFAs and CVD risk factors.